THE DIGITAL DIVIDE: A LOOK INTO TEACHERS AND STUDENTS’ STRUGGLE TO CONECTIVITY - Sri Wahyuni; Uci Sirlianti; Siptia Nurhaliza (Jurnal Media Akademik (JMA), 2026)
The digital divide, defined as the gap between those with access to information and communication technology and those without, remains a significant challenge in education, particularly in Indonesia, where access to technology and digital literacy remains unequal (Ministry of Communication and Informatics & Katadata Insight Center, 2022; Ministry of Education, Culture, Research, and Technology, 2024). This study examines the positive side of the digital divide challenges experienced by teachers and students in the learning process. Using descriptive qualitative methods through a literature review, this study examines various studies published between 2018 and 2025 that focus on issues of connectivity, digital inequality, and how teachers and students adapt in the digital learning era. Although the digital divide is often considered a barrier to equal access to education (Warschauer, 2018; van Deursen & van Dijk, 2019), several studies show that this condition actually encourages innovation, collaboration, and creativity in teaching and learning activities (OECD, 2020; UNESCO, 2021). Teachers are beginning to develop learning strategies that adapt to network limitations, such as blended learning methods and the use of offline media (Almeida & Silva, 2022). Meanwhile, students are becoming more independent, technologically literate, and resilient in the face of changes in the learning system (Miah, 2023; Dabie, 2025). This study concludes that while the digital divide presents challenges, it also presents significant opportunities for educational transformation toward a more creative, adaptive, and sustainable direction